A geography of the Hutterites in North America - Evans, S. M. (University of Nebraska Press, 2021)
Simon M Evans analyzes the German-speaking Anabaptist community, focusing on their history of expansion, their patterns of population growth, the additions they make to the cultural landscape of the northern plains, and their contributions to the agricultural and light manufacturing economies of their home states and provinces.